CLINICAL PARAMETERS OF CHITOSAN ORAL WOUND DRESSING FILM IN THE GINGIVAL INCISIONS OF WISTAR RATS (RATTUS NORVEGICUS) - NURCAHYANTI, HESTY; ERVINA, IRMA; NASUTION, AINI HARIYANI; AGUSNAR, HARRY; SATRIA, DENNY (International Journal of Applied Pharmaceutics, 2025)
Objective: Oral Wound Dressing Film (OWDF) prevents bacterial infections and protects newly formed tissue. The periodontal surgical treatment causes incised wounds, which may result in excessive pain. Periodontal dressings in film preparation are considered easier to apply. Chitosan is effective in accelerating wound healing because it’s mucoadhesive, biocompatible, biodegradable, antimicrobial, and non-toxic properties. The research aims to analyze the effectiveness of Oral Wound Dressing Chitosan Film on clinical Landry's Healing Index and vascularization in the wound healing process after wistar rat gingival incision. Methods: In vivo experimental research with a post-test control group design of 27 male wistar rats in three treatment groups with oral wound dressing film chitosan 2.5%, Ora-Aid®, and placebo. Ora-Aid®used as positive control because it’s widely commercialize tomaintain the humidity in the oral environment and improve wound healing. Clinical parameters were examined with Landry's Healing Index and histological parameters of vascularization on d 3, 7, and 14. Data were analyzed using kruskal-wallis and mann-whitney. Results: There were significant differences in vascularization between the groups on 3rd d (4.20±0.200), 7th d (5.60±0.600) and 14th d (7.20±0.872) with p value<0.05. There were differences in vascularization (p<0.05) between the two groups except for vascularization 3rd d, 7th d and 14th d between Oral Wound Dressing Film chitosan and Ora-Aid® groups (p>0.05). Conclusion: Clinical and vascularization parameters increased after the application of an Oral Wound Dressing Film containing chitosan in the post-gingival incision wound healing process in Wistar rats (Rattus norvegicus).